If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(5y + 2) + -1(-4y + -8) = 1 Reorder the terms: -1(2 + 5y) + -1(-4y + -8) = 1 (2 * -1 + 5y * -1) + -1(-4y + -8) = 1 (-2 + -5y) + -1(-4y + -8) = 1 Reorder the terms: -2 + -5y + -1(-8 + -4y) = 1 -2 + -5y + (-8 * -1 + -4y * -1) = 1 -2 + -5y + (8 + 4y) = 1 Reorder the terms: -2 + 8 + -5y + 4y = 1 Combine like terms: -2 + 8 = 6 6 + -5y + 4y = 1 Combine like terms: -5y + 4y = -1y 6 + -1y = 1 Solving 6 + -1y = 1 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1y = 1 + -6 Combine like terms: 6 + -6 = 0 0 + -1y = 1 + -6 -1y = 1 + -6 Combine like terms: 1 + -6 = -5 -1y = -5 Divide each side by '-1'. y = 5 Simplifying y = 5
| 4-x=-5 | | 2(x+30)= | | 6n-2=14 | | 52=(3x+6)+(6x+22) | | 3(5+x)=31+x | | 51=(2+7x)+(20x+1) | | 50=(8x-6)+(13x+9) | | 87=(8x+2)+(8x+5) | | x-9= | | 8n+8=16 | | 95=(3+8x)+(14x+4) | | 8n+2=16 | | 8n+6=16 | | 8n+6=24 | | 3x+2=7.5 | | 9x+7y=10 | | 57=(9x-2)+(23x-1) | | x+2(x+1)=35 | | 54=(17x+3)+(25x+9) | | 20=(8x+4)+(9x+12) | | 10v+7=8(2u-4)-9 | | 6x+2=8x+14 | | 4(x+1)=8 | | 2p-1=-4p-19 | | (2y-5)-8+y=5 | | 80=(x+9)+(6x-6) | | x^2-42xy-343y^2=0 | | 48=(14x+4)+(24x+2) | | 2b^2+7b=15 | | 2(4p+8)=128 | | x^2+3x-7=0 | | x^2-98=0 |